Flavonoid profiles of some Argentine species of Chuquiraga (Asteraceae). - Mendiondo, Maria Elena (2000)
Chuquiraga avellanedae Lorentz; C. erinacea D. Don; C. erinacea subsp. hystrix (D. Don) C. Ezcurra; C. incana D. Don; C. oppositifolia Don; C. rosulata Gaspar were collected in Mendoza Province, Argentina. A voucher of each specimen is deposited at the Herbarium Ruiz Leal. The voucher numbers are: Chuquiraga avellanedae (MERL 21454); C. erinacea (MERL 11049); C. erinacea subsp. hystrix (MERL 11123); C. incana (MERL 19012); C. oppositifolia (MERL 30473); C. rosulata (MERL 21449).